COMPANY SIZE MODERATING DETERMINANT TAX MANAGEMENT IN TECHNOLOGY SECTOR COMPANIES INDONESIA - Metri Mariana; Mila Afifah; Hakim, Mohamad Zulman; Januar Eky Pambudi; Indra Gunawan Siregar; Reni Anggraeni (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to determine if fixed asset intensity has an effect on leverage, profitability, and tax management in technology companies listed on the Indonesia Stock Exchange in 2021–2023, using the operational size of a corporate entity as a moderating component in the analysis. The study's quantitative approach is predicated on an examination of the yearly financial reports of technology firms that were listed between 2021 and 2023 on the Indonesia Stock Exchange (IDX). There were 44 companies in the population, and through the use of purposive sampling techniques, 13 companies were selected from a total of 44 companies for a detailed investigation for three consecutive years, from 2021 to 2023. Utilizing the statistical program EViews 12, the company's data was analyzed. According to the study's findings, there was no statistically significant correlation found between the leverage ratio and the profitability of the business in tax management, the intensity of fixed assets had a very significant impact. The size of the company cannot control the leverage and profitability in tax management; however, the company's size might regulate how much emphasis is placed on assets in tax management.